Determinación microbiológica y de metales pesados en jugos de alfalfa (Medicago sativa) usado en la preparación de jugos naturales de fruta, expendidos en los diferentes mercados del Distrito Metropolitano de Quito - Quishpe Puga, Karina Marisol (2016)
The natural juice of alfalfa is a popular mixture in Ecuador that is used with medicinal and nutritional purposes. The plant has properties like antihemostatic, appetite stimulant among other uses (Ríos, Koziol, Pedersen, & Granda, 2007). This product is distributed through the metropolitan system of commercialization, but it isn’t has researches which assure its quality. Considering it, we chose the 50% of the metropolitan district territory and found 29 markets that spend process food included this product. With the obtained samples, we realized a chemical composition analysis; it showed that the juices had normal physicochemical characteristics, but they also had pH ranges that prejudice their stability. Furthermore, we realized a determination of two pollutants; they were heavy metals and microorganism. In the first analysis, we found traces of cadmium, cooper and nickel; besides, we found large amounts of lead, an average of 2,6874 mg/Kg. It quantity outpoint national limits. Also, we found a lot of mesophilic microorganisms per cc in all the samples; these amounts exceed the Ecuadorian standard for juices and natural preparations. In addition the 24% of samples had parasitic microorganisms and helminthes. These results evinced the mistakes happened in the preparation of this product in all the samples.